2009
DOI: 10.1016/j.nuclphysa.2009.05.071
|View full text |Cite
|
Sign up to set email alerts
|

The role of the Pauli principle in three-cluster systems composed of identical clusters

Abstract: Within the microscopic model based on the algebraic version of the resonating group method the role of the Pauli principle in the formation of continuum wave function of nuclear systems composed of three identical s-clusters has been investigated. Emphasis is placed upon the study of the exchange effects contained in the genuine three-cluster norm kernel. Three-fermion, three-boson, three-dineutron (3d ′ ) and 3α systems are considered in detail. Simple analytical method of constructing the norm kernel for 3α … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Now let us consider wave functions of trapped and resonance states in the two-cluster systems. Wave functions of the resonance states in 8,7 Be and 6 Li in oscillator and momentum representation are shown in Fig. 5.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Now let us consider wave functions of trapped and resonance states in the two-cluster systems. Wave functions of the resonance states in 8,7 Be and 6 Li in oscillator and momentum representation are shown in Fig. 5.…”
Section: Resultsmentioning
confidence: 99%
“…Wave functions of the trapped state in 5 He, 6 Li and 7 Be in oscillator representation are shown in Fig. 8.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The determination of overlap eigenvalues has also been presented in an algebraic version for three identical clusters in Ref. [38].…”
Section: B Antisymmetrization Effects In 6 Hementioning
confidence: 99%
“…The influence of the Pauli principle on the kinetic energy of relative motion of two clusters has been investigated in Refs. [29,34,32,31]. It has been shown that the kinetic energy of a two-cluster system is not equivalent to the kinetic energy of a two-nucleon system due to the antisymmetrization effects.…”
Section: Introductionmentioning
confidence: 99%